Relevansi Teori Belajar Humanistik Carl Rogers dalam Pendidikan Karakter Perspektif Islam: The Relevance of Carl Rogers' Humanistic Learning Theory in Islamic Perspective Character Education - Zamzami, Alza Nabiel; Putri, Dely Tresia (Thawalib: Jurnal Kependidikan Islam, 2024)
This study aims to analyze the relevance of Carl Rogers' humanistic learning theory in Islamic perspective character education. The type of research used is qualitative research with library research method. The data analysis technique consists of three stages, namely: data condensation stage, data presentation stage, and verification or conclusion drawing stage. The data validity test is carried out using the source triangulation method. Carl Rogers' Humanistic Learning Theory has relevance in the context of Islamic character education. Five important things in the learning process of desire to learn, meaningful learning, learning without punishment, learning by own initiative, and learning and change, provide a useful foundation for the development of students' character and spirituality in accordance with Islamic principles. Both approaches emphasize the importance of active learners, meaningful personal experiences, a positive learning environment, and a continuous process of change. The integration of these two approaches provides a strong foundation for creating more meaningful and effective learning in shaping learners' character in accordance with Islamic teachings that prioritize kindness, justice and compassion in relation to God, fellow humans and the universe. Therefore, the relevance of Carl Rogers' humanistic learning theory in Islamic perspective character education brings a sustainable positive impact in shaping a responsible and noble generation.